Time-dependent tug-of-war games and normalized parabolic p-Laplace equations. (January 2022) - Han, Jeongmin
Abstract: In this paper, we study value functions of time-dependent tug-of-war games. We first prove the existence and uniqueness of value functions and verify that these game values satisfy a dynamic programming principle. Using the arguments in the proof of existence of game values, we can also deduce asymptotic behavior of game values when T → ∞ . Furthermore, we investigate boundary regularity for game values. Thereafter, based on the regularity results for value functions, we deduce that game values converge to viscosity solutions of the normalized parabolic p -Laplace equation.